Technologies to advance automation in forensic science and criminal investigation - Yang, Wen-Chao; Chen, Chung-Hao; Chen, Lijia (A volume in the advances in digital crime, forensics, and, 2022)
This book is focused on technologies to advance automation in forensic science and criminal investigation, including digital evidence and computer technology, photoelectronics, jurisprudence, behavioral science, linguistics, Forensic digital multimedia authentication and origin, cyber security, video surveillance system and technologies used in modern forensics.